Naked look: powers and visual pleasures in Salò by Pier Paolo Pasolini - Marín Villalobos, Roberto (2020)
This article aims to analyze the visual in interplay with nudity, as a catalyst for power and pleasurein the film “Salò o le 120 giornate di Sodoma”, the last work of the director Pier Paolo Pasolini. For this, a discussion is made between scenes from the film and some conceptual postulates. The different uses of nudity and its visual handling not only reflect the aesthetic mastery of the Italian director, but also his theoretical potential to think gaze in Sadean –even sadistic– terms.